Occupy Risk Weighting: How the Minimum Leverage Ratio dominates Capital Requirements - A Swiss Example - Kersten Kellermann; Carsten Schlag (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In September 2009, G20 representatives called for introducing a minimum leverage ratio as an instrument of financial regulation. It is supposed to assure a certain degree of core capital for banks, independent of the controversial procedures used to assess risk. This paper discusses the interaction and tensions between the leverage ratio and risk-based capital requirements, using financial data of the Swiss systemically important bank UBS. It can be shown that the leverage ratio potentially undermines risk weighting such that banks feel encouraged to take greater risks. The paper proposes an alternative instrument that is conceived as a base risk weight and functions as a backstop. It ensures a minimum core capital ratio, based on unweighted total exposure by ensuring a minimum ratio of risk-weighted to total assets for all banks. The proposed measure is easy to compute like the leverage ratio, and also like the latter, it is independent of risk weighting. Yet, its primary advantage is that it does not supersede risk-based capital adequacy targets, but rather supplements them.
Keywords: G28; G21; G01; 330